Questioning The Role Of Supervisors In Supporting The Advance And Quality Of Islamic Education Teacher’s Performance In Satui Area Of Tanah Bumbu Regency - Uswatun Nisa; Selamat Maulana (Tajdid Al-Athfal, 2021)
Supervisors are one of education component that play a role in ensuring and encouraging the advance of early childhood teacher’s about Islamic education performance in both Madrasah and early childhood istitute units. In practice, supervisors do not only function as supervisors but also as facilitators, counselors and motivators in order to create a conducive teaching and learning situation under their supportive environment. This paper is a field type research with a qualitative descriptive that focuses on exploring the role of supervisors including aspects of guidance Islamic education for early childhood teacher in Satui area, Tanah Bumbu regency. Through narratives, words, notes, reports that collected from several selected respondend representations, then enriched with the result of observations, interviews and documentation, also the analysis was conducted through data triangulation techniques; reduction, coding and display. The findings reveal that the duties, roles and functions of supervisors have been carried out regularly/routinely, formally with the specified standards. Especially the implementation of coaching and mentoring in preparing the completeness of learning tools, advancing teacher competence to escorting supervision. However, there are a number of internal and external constraints that can hinder the monitoring process, such as the availability of time, the presence of supervisory resources, and dissemination for the broader forum.